The anatomical and micromorphological structure of Myrtus communis L. leaves - O. Ye. Matsehorova; V. M. Odyntsova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Myrtus communis L. is a promising medicinal plant that has garnered the attention of scientists to introduce it into industrial cultivation as a raw material source for obtaining new phytopreparations. In its chemical composition, Myrtus communis L. contains many biologically active substances, which confer upon it a range of medicinal properties including astringent, anti-inflammatory, antiviral, antibacterial, antifungal, antioxidant, antidiabetic, antiulcer, antimutagenic, gastro- and hepatoprotective properties. Published information primarily focuses on the chemical composition and pharmacological activity of common myrtle, with limited data available on its micromorphology.